Analisis Kelayakan Finanansial Pada Industri Tahu Mitra Cemangi di Kota Palu - Fadli, Fadli; Damayanti, Lien; Sulaeman, Sulaeman (AGROTEKBIS, 2017)
The research aims were to analyze the financial feasibility of âTahu Mitra Cemangiâ industry and to calculate the industry return on invested capital (ROIC).Â  The research was conducted at Tatanga sub district of Palu in January â March 2016.Â  Data was analyzed using financial feasibility analysis with four indicators i.e. net present value (NPV), net benefit cost ration (Net B/C), internal rate of return (IRR), and payback period (PP).Â  During 2012 â 2015, the industry had the NPV of IDR 1,272,519,155, the net B/C of 2.32, the IRR of 41.2%, and the PP of one year and two months.Â  These results suggest that the industry is feasible to operate.Â Keywords: Feasibility, and Financial.